Nutrient optimization for improved in vitro plant regeneration in Eclipta alba (L.) Hassk. and assessment of genetic fidelity using RAPD analysis (Plant Tissue Culture and Biotechnology, 2015)
This study highlights the effect of different inorganic micronutrients like copper, cobalt, molybdenum, zinc, boron, iodine, iron and manganese in accelerating and amplifying in vitro shoot bud induction and proliferation of a medicinally important plant, Eclipta alba (L.) Hassk. Direct shoot bud induction was observed on MS fortified with Kn (2 mg/l). However, maximum number of shoots was achieved when GA3, 0.5 mg/l was added to induction medium along with 1?M copper sulphate (ten times the normal MS level). Optimization of nutrient level in the basal medium promoted maximum regeneration response from both shoot tips and nodal explants. Elongated shoots were rooted in MS supplemented with IBA, 1.0 mg/l. Healthy, green plantlets with well developed roots, flowered normally in the field. Genetic stability of micropropagated plantlets was evaluated using RAPD markers. The amplification products were monomorphic in micropropagated plantlets and similar to those of mother plant revealing the genetic uniformity of plantlets. The regeneration protocol is highly efficient and reproducible so would be useful for mass multiplication, ex situ conservation and genetic transformation of E. alba (L.) Hassk.Plant Tissue Cult. & Biotech. 24(2): 223-234, 2014 (December)